2D and 3D double perovskite with dimensionality-dependent optoelectronic properties: first-principle study on Cs2AgBiBr6 and Cs4AgBiBr8. (17th November 2021) - Chen, Yan-Long; Yan, Dan-Ni; Zeng, Ming-Wei; Liao, Cheng-Sheng; Cai, Meng-Qiu
Abstract: Recently, the effect of dimensional control on the optoelectronic performance of two-dimensional (2D)/three-dimensional (3D) single perovskites has been confirmed. However, how the dimensional change affects the photoelectric properties of 2D/3D all-inorganic double perovskites remains unclear. In this study, we present a detailed theoretical research on a comparison between the optoelectronic properties of 3D all-inorganic double perovskite Cs2 AgBiBr6 and recently reported 2D all-inorganic double perovskite Cs4 AgBiBr8 with Ruddlesden–Popper (RP) structure based on density functional theory calculations. The results demonstrate the charge carrier mobility and absorption coefficients in the visible spectrum of Cs4 AgBiBr8 (2D) is poorer than Cs2 AgBiBr6 (3D). Moreover, the value of exciton-binding energy for 2D RP all-inorganic double perovskite Cs4 AgBiBr8 (720 meV) is 3 times larger than that of 3D all-inorganic double perovskite Cs2 AgBiBr6 (240 meV). Our works indicate that Cs4 AgBiBr8 (2D) is a promising material for luminescent device, while Cs2 AgBiBr6 (3D) may be suitable for photovoltaic applications. This study provides a theoretical guidance for the understanding of 2D RP all-inorganic double perovskite with potential applications in photo-luminescent devices.